Reward Draws the Eye, Uncertainty Holds the Eye: Associative Learning Modulates Distractor Interference in Visual Search - Koenig, Stephan; Kadel, Hanna; Uengoer, Metin; Schubö, Anna; Lachnit, Harald (Frontiers in Behavioral Neuroscience, 2017)
Stimuli in our sensory environment differ with respect to their physical salience, but moreover may acquire motivational salience by association with reward. If we repeatedly observed that reward is available in the context of a particular cue, but absent in the context of another cue, the former typically attracts more attention than the latter. However, we also may encounter cues uncorrelated with reward. A cue with 50% reward contingency may induce an average reward expectancy, but at the same time induces high reward uncertainty. In the current experiment we examined how both values, reward expectancy and uncertainty, affected overt attention. Two different colors were established as predictive cues for low reward and high reward respectively. A third color was followed by high reward on 50% of the trials and thus induced uncertainty. Colors then were introduced as distractors during search for a shape target and we examined the relative potential of the color distractors to capture and hold the first fixation. We observed that capture frequency corresponded to reward expectancy while capture duration corresponded to uncertainty. The results may suggest that within trial, reward expectancy is represented at an earlier time window than uncertainty.